2005
DOI: 10.1089/ten.2005.11.787
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adult Mesenchymal Stem Cells in Bone Tissue Engineering Applications: Current Status and Future Prospects

Abstract: Mesenchymal stem cells (MSCs) have been demonstrated as an attractive cell source for tissue-engineering applications because of their ability to be easily isolated and expanded from adult bone marrow aspirates and their versatility for pluripotent differentiation into mesenchymal tissues. This review highlights advances and progress in bone reconstruction techniques for both the repair of site-specific bone defects and the attenuation of musculoskeletal disease symptoms associated with osteoporosis and osteog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
163
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(170 citation statements)
references
References 172 publications
3
163
0
4
Order By: Relevance
“…Transplanted scaffolds seeded with MSCs have been shown to enhance osteogenic capacity and integrate with native tissue faster than acellular scaffolds in many preclinical trials. [32][33][34][35] A primary obstacle in translating this technology from the bench to the bedside is that this technique involves an additional surgery and the patient must wait for the bone graft to develop in vitro. Therefore, to promote the rapid development of a transplant-ready cellular scaffold, a variety of novel ex vivo culture techniques have been investigated to accelerate the cellular production of ECM.…”
Section: General Principles In Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplanted scaffolds seeded with MSCs have been shown to enhance osteogenic capacity and integrate with native tissue faster than acellular scaffolds in many preclinical trials. [32][33][34][35] A primary obstacle in translating this technology from the bench to the bedside is that this technique involves an additional surgery and the patient must wait for the bone graft to develop in vitro. Therefore, to promote the rapid development of a transplant-ready cellular scaffold, a variety of novel ex vivo culture techniques have been investigated to accelerate the cellular production of ECM.…”
Section: General Principles In Bone Tissue Engineeringmentioning
confidence: 99%
“…The first and most significant barrier is that a number of studies have shown that MSCs which have been extensively cultured ex vivo lose their phenotypic behavior (such as osteodifferentiation and bone forming capacity) once implanted in vivo. 33,44,45 Secondary challenges confronted in this approach are related to the relative low concentration of MSCs in bone marrow and their characteristic low proliferative capacity making it difficult to obtain sufficient cell density in a large scaffold. 46,47 In addition to the increased risk due to a second surgery, there is a need to establish rigorous sterilization techniques for the cell-seeded scaffold which has been in culture ex vivo for up to several weeks.…”
Section: General Principles In Bone Tissue Engineeringmentioning
confidence: 99%
“…These endogenous progenitor cells can be mobilized to the PB [1,11,12,15,17,22,36,48,52]. Circulating MSCs, and perhaps other adult stem cells, home to sites of skeletal injury [14,23,29,35,45,54], and increasing the number of adult stem cells at sites of injury aids tissue regeneration [4,8,16,40,43,56] either directly or through trophic effects [5,8,17,53].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2001) demonstrated that the preoperative treatment with VEGF induced angiogenesis and enhanced skin paddle survival. In addition, the use of stem cell tissue engineering has emerged as an efficient approach for various therapeutic purposes due to the ability of self-renewal and multiple differentiation into osteogenic, adipogenic, myogenic, chondrogenic and other cell lineages (Cancedda et al 2003;Tuan 2004;Mauney et al 2005). MSCs have been widely studied and show great efficiency in clinical applications (Hong et al 2006(Hong et al , 2011.…”
Section: Discussionmentioning
confidence: 99%